Pengaruh Pelayanan Fiskus, Pemahaman Pajak dan Preferensi Risiko Terhadap Kepatuhan Wajib Pajak - Anissa Yuniar Larasati; Wiwi Hartika (Jurnal Akuntansi, 2023)
Since 1983 Indonesia has carried out tax reforms where the tax payment procedure haschanged from official assessment to self-assessment system. Self-assessment system givesfull trust and responsibility to the taxpayer community to fulfill their tax obligations. Toincrease tax awareness is important in increasing state revenue. The services of tax officersare also very important in influencing taxpayers. Because the quality of service mustachieve the expected goal of increasing taxpayer satisfaction and taxpayer compliance. Theresearch method uses descriptive research methods through a quantitative approach. Thedata collection technique used in this study, namely primary data. Primary data is obtainedthrough questionnaire techniques that are distributed to individual taxpayers in the KPPPratama Cimahi area. And it will be tested using SPSS v.21. Theeresults of the study foundthat fiscus services have no effect on taxpayer compliance, tax understanding has aninfluence on taxpayer compliance, and risk preferences have no effect on taxpayercompliance.Keywords: Fiscus Ministry, Tax Understanding, Risk Preferences, Taxpayer Compliance